Communicative challenges in the home care of older persons – a qualitative exploration. (4th May 2016) - Sundler, Annelie J.; Eide, Hilde; van Dulmen, Sandra; Holmström, Inger K.
Abstract: Aim: To explore communicative challenges in encounters between nurse assistants and older persons during home care visits. Background: The older population is increasing worldwide. Currently, there is a shift in care for older people from institutional care to home care. Providing home care in a person's home involves several challenges, including the complexity of communication. Design: A descriptive observational design with a qualitative approach was used. Methods: The data consisted of audio recordings of real‐life encounters during home care visits between nurse assistants and older persons, collected in 2014. A hermeneutic phenomenological analysis was conducted. Results: Communicative challenges were identified: (a) in situations where the older persons had a different view than the nurse assistants on the care task and its content; and (b) when unexpected actions or turns occurred in the communication. Challenges included older person's existential issues, fragility and worries and concerns, which often appeared to be only vaguely expressed and difficult to verbally detect and tackle. This engendered a risk of misinterpretation or ignorance of these challenges. Conclusion: The findings point to the importance of communication as the key to facilitate person‐centred home care. Communication training should focus more on addressing needs and existential issues in older persons. Person‐centred home care for older persons needs to be addressed at both an individual and an organizational level.